Synthesis and spectroscopic properties of β-triazoloporphyrin–xanthone dyads - Singh, Dileep Kumar; Nath, Mahendra (Beilstein Journal of Organic Chemistry, 2015)
A novel series of β-triazoloporphyrin–xanthone conjugates and xanthone-bridged β-triazoloporphyrin dyads has been synthesized in moderate to good yields through Cu(I)-catalyzed Huisgen 1,3-dipolar cycloaddition reaction of copper(II) 2-azido-5,10,15,20-tetraphenylporphyrin or zinc(II) 2-azidomethyl-5,10,15,20-tetraphenylporphyrin with various alkyne derivatives of xanthones in DMF containing CuSO4 and ascorbic acid at 80 °C. Furthermore, these metalloporphyrins underwent demetalation under acidic conditions to afford the corresponding free-base porphyrins in good to excellent yields. After successful spectroscopic characterization, these porphyrins have been evaluated for their photophysical properties. The preliminary results revealed a bathochromic shift in the UV–vis and fluorescence spectra of these porphyrin–xanthone dyads.
Keywords: 1,3-dipolar cycloaddition; fluorescence; synthesis; triazoloporphyrin-xanthone dyads; UV–vis spectroscopy